2014
DOI: 10.1111/1750-3841.12585
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Sensory and Oxidative Stability of Cooked and Chill‐Stored Lamb Using Dietary Rosemary Diterpenes

Abstract: Two dietary rosemary extracts (DREs) containing diterpenes (carnosic acid and carnosol at 1:1 and 2:1 w:w) were tested in fattening lambs to stabilize the sensory quality of cooked and chill-stored patties. A total of 63 lambs were fed freely for 80 ± 5 d with a basal diet supplemented or not with DRE. Minced leg meat from each lamb was used to make patty batches. The patties were cooked at 72 ºC for 2 min, aerobically packed, kept at 2 ºC for up to 4 d and then reheated. Sensory traits (color, odor, flavor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…StabilRose TM range of de-odorized and decolorized rosemary antioxidants used in the present Since diterpenes may contribute to the unpleasant flavor characteristics, care was taken to keep the 12-Omethyl carnosic acid content low and to maintain a definite ratio of carnosic acid content to the total diterpenes in StabilRose extracts. The ratio of carnosic acid to carnosol was maintained at 1:1 level, in accordance with the early reports for better efficacy (Serrano et al 2014). …”
Section: Resultssupporting
confidence: 90%
“…StabilRose TM range of de-odorized and decolorized rosemary antioxidants used in the present Since diterpenes may contribute to the unpleasant flavor characteristics, care was taken to keep the 12-Omethyl carnosic acid content low and to maintain a definite ratio of carnosic acid content to the total diterpenes in StabilRose extracts. The ratio of carnosic acid to carnosol was maintained at 1:1 level, in accordance with the early reports for better efficacy (Serrano et al 2014). …”
Section: Resultssupporting
confidence: 90%
“…Lauzurica et al (2005) reported that metmyoglobin was inhibited following 250-1000 mg dietary vitamin E kg − 1 supplementation in chilled-lamb loin packed under 70/30 O 2 /CO 2 MAP for up to 28 days. In addition, color (assessed as CIELab color and by sensory descriptive analysis) was also stabilized using 200-600 mg of different DREs per kg feed in Segureño lamb loin processed under similar retailing conditions to those of the present study (Bañón et al, 2012;Ortuño et al, 2014;Serrano et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Among the tested rosemary derivatives used in animal feeding, oil-free extracts provided effectual and steady results, probably due to their lack of heterogeneity and the possibility of adjusting the desired proportion of active compounds. For example, raw lamb shelf life was extended by up to 4 days when the lamb diet was supplemented with 200-600 mg diterpenes kg −1 feed (Bañón et al, 2012;Ortuño et al, 2014;Serrano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…137,138 Rosemary extracts acted as an effective antioxidant when introduced to lamb diets, and also stabilized the sensory quality, TBARS value and color of cooked and chill-stored patties, without the addition of synthetic preservatives. 139 Similarly, the addition of rosemary and -tocopherol acetate to chicken diets revealed that both improved the oxidative stability of meat. 140 Despite many positive results, several commercially manufactured rosemary-based products such as oleoresin were not as effective at reducing lipid oxidation, resulting in various divergences in literature.…”
Section: Condiments Leaves Herbs and Spicesmentioning
confidence: 99%